PRAKTIK PEKERJA SOSIAL DALAM PENDAMPINGAN MASA PERSIDANGAN ABH DI SENTRA HANDAYANI JAKARTA - Faisyahril, Ria (Program Studi Pendidikan Masyarakat, Universitas Mulawarman, 2024)
The adolescent development dynamics sometimes lead to behaviors that violate the rules, which are generally in the form of juvenile delinquency. In many cases of juvenile delinquency, the impact has entered the legal realm, where what they do violates the rules and gets criminal law, so they are called Children Facing the Law (ABH). This study aims to look at the practice of social workers in handling ABH clients, drug dealers and users in Sentra Handayani. The method used is qualitative with block placement. The practical steps of social workers seen in the micro realm are engagement, assessment, intervention plan, intervention, evaluation, and termination. As a result, there was a decrease in anxiety after intervention by social workers. In addition, the presence of social workers is also able to facilitate the process of implementing protection for ABH and their families. The intervention carried out by social workers in this institution is considered to be able to ensure that the justice system for ABH does not ignore the needs and rights of children, but on the other hand also provides appropriate justice for criminal offenders.